2018
DOI: 10.1038/s41586-018-0498-z
|View full text |Cite
|
Sign up to set email alerts
|

A flavin-based extracellular electron transfer mechanism in diverse Gram-positive bacteria

Abstract: Extracellular electron transfer (EET) describes microbial bioelectrochemical processes in which electrons are transferred from the cytosol to the exterior of the cell. Mineral-respiring bacteria use elaborate haem-based electron transfer mechanisms but the existence and mechanistic basis of other EETs remain largely unknown. Here we show that the food-borne pathogen Listeria monocytogenes uses a distinctive flavin-based EET mechanism to deliver electrons to iron or an electrode. By performing a forward genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
505
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(523 citation statements)
references
References 54 publications
15
505
3
Order By: Relevance
“…The hydrolysis of FAD to FMN with incorporation into a membrane protein was recently proposed for other Gram-positive bacteria (Buttet et al, 2018). Additionally, a flavin-based extracellular electron transfer mechanism was proposed for Gram-positive bacteria, in which FAD is converted to FMN, which is bound to a predicted extracellular electron transfer lipoprotein (Light et al, 2018). Another possibility is that FAD itself gets incorporated in an insoluble enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrolysis of FAD to FMN with incorporation into a membrane protein was recently proposed for other Gram-positive bacteria (Buttet et al, 2018). Additionally, a flavin-based extracellular electron transfer mechanism was proposed for Gram-positive bacteria, in which FAD is converted to FMN, which is bound to a predicted extracellular electron transfer lipoprotein (Light et al, 2018). Another possibility is that FAD itself gets incorporated in an insoluble enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis could be that, it is a result of flavin transport in C. acetobutylicum, which limits the cycling of FMN and FAD if added exogenously. Flavin transporters have not been characterized in C. acetobutylicum but the bacterium encodes genes whose corresponding proteins show homology with RF importers in other Firmicutes (Light et al, 2018). As mentioned above, a recent study reported increased RF concentrations in the culture supernatant of a fur mutant or iron-deficient culture suggesting a correlation between RF trafficking and iron availability.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the intense study of microbial nanowires (Malvankar et al, 2011;Reguera et al, 2005;Wang et al, 2019), less attention has been paid to how small soluble (physically diffusive) extracellular electron shuttles facilitate EET beyond interactions at the cell surface (Light et al, 2018;Marsili et al, 2008;Xu et al, 2016). In part, this neglect is due to the challenges involved in identifying and studying small molecule metabolites, compared to the multiheme cytochromes observed in many genomes of organisms known to engage in EET.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly in Shewanella sp., the secretion of flavin mononucleotide and riboflavin contributes greatly to EET . Flavins also mediate EET in hundreds of Gram‐positive bacterial species within the Firmicutes . A broad range of exogenous quinone analogues can be used to mediate photosynthetic EET (see below), showing that this class of molecule can in principle function as a mediator.…”
Section: Features Of Biophotovoltaic Systemsmentioning
confidence: 99%
“…[67][68][69] Flavins also mediate EET in hundreds of Gram-positive bacterial species within the Firmicutes. [70] A broad range of exogenous quinone analogues can be used to mediate photosynthetic EET [71] (see below), showing that this class of molecule can in principle function as a mediator. It therefore seems likely that at least some cyanobacteria may use a molecule such as a quinone or a flavin for endogenous IEET.…”
Section: Endogenous Eet Mechanismsmentioning
confidence: 99%